Effect of low‐intensity exercise with blood flow restriction during rest intervals on muscle function and perception. (11th July 2022) - Tanaka, Tsukasa; Kubota, Atsushi; Nozu, Shojiro; Ozaki, Hayao; Kishimoto, Kohei; Nishio, Hirofumi; Takazawa, Yuji
Abstract: Purpose: We assessed the effects of low‐intensity exercise with blood flow restriction (BFR) during rest intervals on recovery of muscle function and pain during exercise and rest intervals. Methods: Participants were 10 males and study arms of the participants were randomly assigned into three conditions; low‐intensity exercise with BFR during rest intervals (rBFR), low‐intensity exercise with BFR during exercise (eBFR) and low‐intensity exercise only (EO). The exercise task was elbow flexion until repetition failure at 30% of 1 RM and cuff pressure was 120 mmHg. The maximum voluntary isometric contraction (MVIC) and the muscle endurance (ME) were measured pre, post, 1, 24 and 48 h after the exercise. Pain during exercise and rest intervals were evaluated using the Numerical Rating Scale. Results: MVIC and ME significantly decreased after exercise in all conditions. Pain during exercise was lower in rBFR (4.2 ± 2.9) ( p  = 0.007) and EO (4.4 ± 2.7) ( p  = 0.014) conditions compared to eBFR condition (6.7 ± 1.7), but the pain during rest intervals was more intense in rBFR condition (5.2 ± 1.6) compared to eBFR (1.5 ± 1.4) and EO (1.7 ± 1.2) conditions ( p  < 0.001). Conclusion: We discovered that recovery of muscle function was the same as BFR during rest intervals and BFR during exercise. Also, our results suggested that BFR itself may cause the perception of pain. Future studies are thus required to investigate the optimal dosage focusing on the pressure volume and intensity used in BFR during intervals.